(untitled) (Journal of Intellectual Property Rights (JIPR), 2026)
The evolution of character merchandising from its initial role as an adjunct to exploiting the distinctive traits of real or fictional personalities has resulted in significant revenue generation. However, stakeholders in India’s entertainment landscape have encountered legal disparities amidst this evolution. This article elucidates the legal intricacies of character merchandising, focusing on celebrity or personality merchandising. It examines the inherent conflicts among Indian laws governing character merchandising and analyzes recent judicial developments, and the need for a balanced dispute resolution framework between copyright holders and celebrities. Through this analysis, the article provides valuable insights into navigating legal challenges and fostering equitable solutions in character merchandising within India’s evolving legal framework. It delves into recent judicial pronouncements about character merchandising within the Indian legal landscape and examines the existing legal framework. Moreover, the study endeavors to devise a framework for harmonizing the interests of copyright holders and celebrities within the realm of character merchandising.